Population Dynamics and Food Preferences of the Testate Amoeba Nebela tincta major-bohemica-collaris Complex (Protozoa) in a Sphagnum Peatland - Gilbert, Daniel; Mitchell, Edward; Bourdier, Gilles; Francez, André-Jean (My University, 2003)
Population dynamics and food preferences of the testate amoeba species complex Nebela tincta major-bohemica-collaris ("Nebela collaris sensu lato") were described from a Sphagnum peatland over one growing season. The average abundance of Nebela collaris sensu lato was 29582 ind. l-1 active, and 2263 ind. l-1 encysted forms. On average, 17.4% of Nebela collaris sensu lato specimens were observed associated with prey, 71% of which could not be identified because of their poor preservation state. Among the identified prey, those most frequently ingested were micro-algae (45% of the total predator-prey associations, especially diatoms: 33%), and spores and mycelia of fungi (36%). Large ciliates, rotifers and small testate amoebae were also ingested, but mainly in summer. The seasonal variations in the proportions of prey categories in the ecosystem and the percentage of identifiable prey lead us to hypothesise that (1) Nebela collaris sensu lato ingest mainly immobile, senescent or dead organisms, and (2) that the more mobile micro-organisms such as ciliates and microMetazoa become more accessible, in relatively dry conditions, when the water film is thin.